Beyond IgE—When Do IgE-Crosslinking and Effector Cell Activation Lead to Clinical Anaphylaxis? - Poulsen, Lars K.; Jensen, Bettina M.; Esteban, Vanesa; Garvey, Lene Heise (Frontiers in Immunology, 2017)
Anaphylaxis in humans is inherently difficult to study due to the acuteness of symptoms, and the lack of biomarkers serving as risk predictors. Most cases are related to IgE-sensitizations to foods, insect venoms and drugs with mastocytosis patients forming a smaller risk group. Identifying the relatively small fraction of persons at risk has been exceedingly difficult, however. In this review, we propose to describe anaphylaxis in a broader context than defined by IgE-sensitisation alone. Exposure to a trigger, such as an allergen, may lead to anaphylaxis, but in particular the internal dose sensed by the immune system needs to be established. Moreover, intrinsic patient factors as well as the specific circumstances of the exposure, i.e. the extrinsic factors, needs to be thoroughly accounted for. More controversially, other triggers of anaphylaxis, such as increased sensitivity to or reduced catabolism of histamine ("histamine intolerance") or Mast Cell Activation Syndrome (MCAS) also named mast cell activation disorder (MCAD) have been suggested, but still with very limited epidemiological evidence that a significant proportion of the observed reactions are caused by these alleged conditions. Thus, when all conditions are considered, it seems as if IgE-mediated reactions are responsible for the vast majority of anaphylactic conditions.